Taboo language translation in the Lithuanian voice-over of the film The 40-Year-Old Virgin (2005) - Veitaitė, Neilina; Satkauskaitė, Danguolė (Transletters. International Journal of Translation and Interpreting, 2025)
This study examined the translation of taboo words in the Lithuanian voice-over of Judd Apatow’s American romantic comedy film The 40-Year-Old Virgin (2005). The objectives were to categorize taboo words, determine their functions, and analyze the translation strategies used in the Lithuanian version 40-ties ir vis dar skaistus. Employing qualitative and quantitative methods, this study followed Swan’s (2015) classification of taboo words and their functions, and Pavesi and Formentelli’s (2023) translation strategies. The results indicated that the dominant category was sexual activity, with insults and exclamations expressing annoyance as prominent functions. Most taboo words were mitigated or omitted in the translation.